2014
DOI: 10.1177/0969733013518448
|View full text |Cite
|
Sign up to set email alerts
|

Informed consent, vulnerability and the risks of group-specific attribution

Abstract: People in extraordinary situations are vulnerable. As research participants, they are additionally threatened by abuse or exploitation and the possibility of harm through research. To protect people against these threats, informed consent as an instrument of self-determination has been introduced. Self-determination requires autonomous persons, who voluntarily make decisions based on their values and morals. However, in nursing research, this requirement cannot always be met. Advanced age, chronic illness, co-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 39 publications
1
49
0
2
Order By: Relevance
“…National Statement)Vulnerable because: • Vulnerability may arise because of discovery of participants’ illegal activity [34] Those with diminished capacity for self-determination (TCPS2) • Historically vulnerable and “have, at times, been treated unfairly and inequitably in research, or have been excluded from research opportunities” a ([35], p. 8) The least organizationally developed communities (TCPS2)Vulnerable to: • Exploitation [35]Grouped by patient/participant condition Children, minors, or young people (CIOMS, Clinical Trials Directive, Clinical Trials Regulation, Aus. National Statement, TCPS2, Common Rule)Vulnerable because: • Limited freedom or capacity to consent [29, 35] • Vulnerability arising from developmental stage [35] • No explanation [31, 32] • Explanation unclear [34]Vulnerable to: • Coercion or undue influence [38] Persons with mental illness or mental health problems (Clinical Trials Regulation, Aus. National Statement, TCPS2, UK Research Governance Framework)Vulnerable because: • Historically considered vulnerable and “have, at times,  been treated unfairly and inequitably in research, or  have been excluded from research opportunities” a ([35], p. 8) • Unclear [32, 36]Vulnerable to: • Various forms of discomfort and stress [34] Elderly persons (CIOMS, Clinical Trials Regulation, TCPS2)Vulnerable because: • Likely to acquire “vulnerability-defining” traits (e.g., institutionalization, dementia) ([29], p. 65] • Historically considered a group in vulnerable circumstances “have, at times, been treated unfairly and inequitably in research, or have been excluded from research opportunities” a ([35], p. 8) • No explanation [32] Persons with limited (or no) freedom or capacity to consent (CIOMS, Clinical Trials Regulation, ICH GCP)Vulnerable because: • Relatively (or absolutely) incapable of protecting their own interests [29] • No explanation [32] • Explanation unclear [33]Vulnerable to: • Exploitation for financial gain by guardians [29] Pregnant or breastfeeding women (Clinical Trials Regulation, Common Rule)Vulnerable to: • Coercion or undue influence [38] • No explanation [32] Adults with learning difficulties (UK Research Governance Framework) • No explanation [36] Handicapped persons (Common Rule) • No explanation [38] Mentally disabled persons (Common Rule)Vulnerable to: • Coercion or undue influence [38] Pers...…”
Section: Resultsmentioning
confidence: 99%
“…National Statement)Vulnerable because: • Vulnerability may arise because of discovery of participants’ illegal activity [34] Those with diminished capacity for self-determination (TCPS2) • Historically vulnerable and “have, at times, been treated unfairly and inequitably in research, or have been excluded from research opportunities” a ([35], p. 8) The least organizationally developed communities (TCPS2)Vulnerable to: • Exploitation [35]Grouped by patient/participant condition Children, minors, or young people (CIOMS, Clinical Trials Directive, Clinical Trials Regulation, Aus. National Statement, TCPS2, Common Rule)Vulnerable because: • Limited freedom or capacity to consent [29, 35] • Vulnerability arising from developmental stage [35] • No explanation [31, 32] • Explanation unclear [34]Vulnerable to: • Coercion or undue influence [38] Persons with mental illness or mental health problems (Clinical Trials Regulation, Aus. National Statement, TCPS2, UK Research Governance Framework)Vulnerable because: • Historically considered vulnerable and “have, at times,  been treated unfairly and inequitably in research, or  have been excluded from research opportunities” a ([35], p. 8) • Unclear [32, 36]Vulnerable to: • Various forms of discomfort and stress [34] Elderly persons (CIOMS, Clinical Trials Regulation, TCPS2)Vulnerable because: • Likely to acquire “vulnerability-defining” traits (e.g., institutionalization, dementia) ([29], p. 65] • Historically considered a group in vulnerable circumstances “have, at times, been treated unfairly and inequitably in research, or have been excluded from research opportunities” a ([35], p. 8) • No explanation [32] Persons with limited (or no) freedom or capacity to consent (CIOMS, Clinical Trials Regulation, ICH GCP)Vulnerable because: • Relatively (or absolutely) incapable of protecting their own interests [29] • No explanation [32] • Explanation unclear [33]Vulnerable to: • Exploitation for financial gain by guardians [29] Pregnant or breastfeeding women (Clinical Trials Regulation, Common Rule)Vulnerable to: • Coercion or undue influence [38] • No explanation [32] Adults with learning difficulties (UK Research Governance Framework) • No explanation [36] Handicapped persons (Common Rule) • No explanation [38] Mentally disabled persons (Common Rule)Vulnerable to: • Coercion or undue influence [38] Pers...…”
Section: Resultsmentioning
confidence: 99%
“…First, the results obtained from consenting subjects could not be generalized to subjects who are unable to provide consent (i.e., in coma). It is noteworthy that patients capable of providing consent might have a greater chance of full recovery in comparison to subjects incapable of providing consent, or they may be less susceptible to the risks of the treatment (Schrems 2014). A.…”
Section: Fda Regulations (21 Cfr 5024) For a Waiver Of Informed Consmentioning
confidence: 99%
“…El-Menyar et al Moreover, we should not exclude vulnerable cases from research projects, as this will affect their needs and violate the ethical principles of justice and beneficence. If we consider vulnerability as a context-related and situational concept with the existing approaches to informed consent, the ethical principles can be balanced and preserved during the entire research process, as has been recently reported by Schrems (2014).…”
Section: Recommendations and Conclusionmentioning
confidence: 99%
“…Ethical dilemmas in both including and excluding ''vulnerable people'' in qualitative nursing research are discussed, 9 since the exclusion of ''vulnerable people'' from research projects would disadvantage these people by not covering their needs, which would also violate the ethical principles of justice and beneficence. 10 All in all, guidelines are constructed in order to protect people from misuse of register data and other personal sensitive data, and to ensure ethical practice in all research including qualitative research.…”
Section: Introductionmentioning
confidence: 99%
“…Second, an often claimed mismatch is the mismatch between the ethical guideline of informed consent which is based on individual rights and justice related to the principle of voluntariness, 3 and qualitative research which often takes place in collectivistic settings. 9,10,12 Ethical knowledge in qualitative research develops from relationship in a certain situation between at least two persons, and a research relation is a responsive relationship in an ongoing decision-making process. Third, a common claimed mismatch is between guidelines which are standardized and the fact that qualitative empirical research is performed at a certain place and time.…”
Section: Introductionmentioning
confidence: 99%